Risk factors predictive of post-abortion distress demonstrate that most abortions are contraindicated: A retrospective cross-sectional study - David Reardon; Martha Shuping; Patricia Giebink (Issues in Law & Medicine, 2026)
Introduction: The subgroup of women at highest risk of post-abortion distress can be identified using known risk factors. At highest risk are women who feel pressured to undergo unwanted abortions. But abortion providers seldom screen for these, which violates ethical principles of informed consent and of justice. This study examines the effectiveness of an 8-item scale for risk assessment. Materials and methods: Topic blind surveys were distributed to a random sample of 41- to 45-year-old women. Reproductive histories were assessed, with 22.6% reporting a history of abortion, a rate comparable to national averages. Respondents reporting abortions were queried on risk factors and rated the degree, if any, they attributed any of six negative outcomes to their abortions. Negative outcomes and the maximum harm identified by each respondent were analyzed using correlations, distributions along a constructed risk scale, and Bayesian regression analyses in relation to their self-reported risk factors and abortion decision types. Results: Risk factors reported as present prior to an abortion were strongly correlated to more negative outcomes. Our 8-item constructed risk scale closely tracked the degree of maximum harm respondents attributed to their abortions. The mean risk scale scores were 2.46 for women whose abortions were wanted, 4.47 for women whose abortions were accepted but inconsistent with their preferences, 5.56 for those whose abortions were unwanted, and 6.68 for those who reported being coerced. Bayesian models revealed that the risk factors explained 50 percent or more of the negative outcomes. Conclusions: Women considering abortions should be evaluated for risk factors predictive of negative outcomes. The failure to screen for these risk factors is medical negligence. Screening and informing women of their personal risk factors as required by ethical and legal standards may lead to consideration of alternatives to abortion by women who consider the risks unacceptable. Keywords: induced abortion; risk factors; decision making; counseling; adjustment disorders; evidence-based practice; pre-abortion screening, informed consent.